"Reading Is Important, " but "I Don't Read": Undergraduates' Experiences With Academic Reading. Issue 5 (26th September 2019) - Gorzycki, Meg; Desa, Geoffrey; Howard, Pamela J.; Allen, Diane D.
Abstract: Qualitative data analysis from open‐ended comments written by 206 undergraduates illustrates student attitudes, beliefs, and practices that reveal an academic reading paradox. Consistently, undergraduates report that reading is valuable, yet their noncompliance with reading assignments suggests otherwise. Undergraduates report that they achieve their academic goals with little reading and that they perceive reading as too voluminous and irrelevant to class outcomes. The data highlight a misalignment between conventional academic expectations that undergraduates will read in scholarly ways and their actual academic reading practice. Qualitative analysis illustrates that students do not experience academic reading as a venue for scholarly engagement in disciplinary discourse. Whereas the academic reading literature proposes that students develop along a continuum from novice to expert reader, findings suggest that the undergraduate experience of academic reading is not representative of that continuum.